THE IDEAL TEACHER FIGURE ACCORDING TO IMAM AL-GHOZALI (STUDY OF THE BOOK OF IHYA' ULUMUDDIN) - Siskiyah, Siskiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Teacher as one disseminator Education component values humanity in the learning process teach, follow role in business formation source Power man potential and quality. because that, the teacher must follow as well as in a manner active and put position as appropriate professional staff with circumstances growing society growing. Each teacher lies not quite enough answer For bring participant teach him to maturity or level maturity certain in matter this teacher does solely as teacher who does transfer of knowledge, but also do transfer of values and all at once transfer of skills. So from That ideal teacher figure is needed as an ideal role model character and education. One of the famous shops in the field of Islamic religious education is Imam Al- Ghozali with his work, ihya’ ulumuddin capable convey with clear regarding ideal teachers and participants ideal student too. According to Imam Al- Ghozali that The ideal teacher figure is a teacher other than smart and perfect reason is also a good teacher moral and strong physical, with perfection sense He can own various knowledge knowledge in a manner deep and with good morals can become examples and examples for the participants educate as well as with strong his physique He can carry out task teach, educate and direct participant he taught. Research results This show that For become the ideal teacher in view of Imam Al- Ghozali requires five competencies that is knowledge, skills, attitudes, role models, ethics. And also work teach is activities that are most needed and most perfect role, because a teacher perfects and purifies heart most important human a teacher should guide child teach them to have faith and piety to God swt.